Promotion to Learning Organization of School Administrators Under the Phang Nga Provincial Office of Learning Encouragement. - จันทร์ทอง, ชาญชัย; Wangjam, Sangwan; Yomsungnoen, Junchai; Suttasiri, Surasak (Journal of MCU Phetchaburi Review, 2026)
This independent research aimed to study the Promotion to Learning Organization of School Administrators Under the Phang Nga Provincial Office of Learning Encouragement. The population consisted of 115 individuals, along with 5 experts selected for purposive interviews. The research instruments included questionnaires and interview guides. Data was analyzed using means, standard deviations, and content analysis. The research findings indicated that the overall promotion of learning organization by school administrators was at a high level. Considering each aspect individually, all items were at a high level, as follows: the implementation of learning organization promotion, followed by the planning of learning organization promotion, and the improvement and development of learning organization promotion. The aspect with the lowest mean score was the monitoring of learning organization promotion. Recommendations for development include: 1) School administrators should take a strategic role in setting direction and driving initiatives by systematically linking policy to practice; 2) Promote the school's knowledge base as a living learning resource capable of systematically collecting, exchanging, and expanding knowledge; 3) Continuously and systematically drive collaborative learning through PLC (Professional Learning Community) processes; 4) Promote the development of a flexible, modern, and continuously reflecting progress monitoring and evaluation system; and 5) Promote the use of technology and the creation of innovations for sustainable change, using the participation of all sectors as a key mechanism. 6) Use the evaluation results as feedback for continuous improvement and development of operations. 7) Encourage teachers to think creatively, experiment, and conduct classroom research, while also fostering collaboration with the community and partner networks.